2021
DOI: 10.3390/su13063572
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Dietary Habits, Physical Activity and Lifestyle in Medical University Students

Abstract: A busy schedule and demanding tasks challenge medical students to adjust their lifestyle and dietary habits. The aim of this study was to identify dietary habits and health-related behaviours among students. A number of 403 students (80.40% female, aged M = 21.21 ± 4.56) enrolled in a medical university provided answers to a questionnaire constructed especially for this research, which was divided into three parts: the first part collected socio-demographic, anthropometric, and medical data; the second part in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 70 publications
1
10
0
1
Order By: Relevance
“…Simi-larly, in the previous study of Australian university students from a range of study fields, 40% were overweight or obese, and 38% were insufficiently active [5]. Among Romanian medical students, however, only ~13% were overweight or obese and ~3.2 h per week was spent engaged in physical activity [52]. This latter study is more consistent with our findings, suggesting that biomedical students engage in healthier lifestyle practices than the general young adult and university student population.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Simi-larly, in the previous study of Australian university students from a range of study fields, 40% were overweight or obese, and 38% were insufficiently active [5]. Among Romanian medical students, however, only ~13% were overweight or obese and ~3.2 h per week was spent engaged in physical activity [52]. This latter study is more consistent with our findings, suggesting that biomedical students engage in healthier lifestyle practices than the general young adult and university student population.…”
Section: Discussionsupporting
confidence: 89%
“…Consumption of EDNP foods was associated with more frequent purchasing of foods and drinks on-campus [7]. Among students enrolled in a nutrition class in Australia [49], consumption of takeaway food was less frequent than that reported in other studies in young adults [50,51], and, in a cohort of Romanian medical students, the majority reported that they consumed fast food either not at all or only once per week [52]. Furthermore, a Spanish study comparing biomedical and non-biomedical university students reported that biomedical students made healthier food choices [19].…”
Section: Discussionmentioning
confidence: 73%
“…Dietary habits established by both teenagers and young adults had a long-term impact on behavior and had a significant impact on adult life. Mealtime etiquette was extremely crucial for physical well-being [15]. Statistical analysis showed in Table 2 that more than half of the subjects complied with the normal 2-3 meals a day (63.71%, N = 1050) and only (0.30%, N = 5) students mentioned that they did not eat daily.…”
Section: Dietary Habits and Cigarette Consumptionmentioning
confidence: 99%
“…Moreover, because young adults can play essential roles in society (e.g., physicians, lawyers, health ministers, police officers), as well as decisionmakers and having significant behavior patterns and attitudes, the health and lifestyle habits of university students were of interest to public health [15]. Because of this, it was vital to take action to improve nutrition knowledge, particularly regarding healthy lifestyle/habits and physical education.…”
Section: Original Articlementioning
confidence: 99%
“…Researchers have identified that healthcare students have an increased focus on their own health, practice a better lifestyle compared to other student populations, and have a favorable perception of their own health and body [ 12 , 13 ]. The strong relationship between healthy lifestyle, body image, and healthy behaviors is interrelated with mental health [ 9 ].…”
Section: Introductionmentioning
confidence: 99%